Analisis Faktor Internal Yang Mempengaruhi Underpricing Saham Pada Initial Public Offering (Studi Perseroan Go Public di BEI Januari- Desember 2019) - Yandes, Jufri; Destiana, Destiana (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2023)
This study was carried out to examine internal factors that determine the underpricing value of shares in the initial public offering on the IDX (Indonesia Stock Exchange) for the period January – December 2019. These internal factors consist of ROA (Return on Asset) and ROE (Return on Equity). This study is quantitative, and uses the explanatory research type of study, and uses the purposive sampling method in determining the sample. The sample used was 32 issuers during the period January – December 2019. The method used in this study is hypothesis testing including multiple linear regression analysis using the help of the Statistical Program for Social Science (SPSS). The database used in this study is a prospectus data published by issuers that will go public in collaboration with underwriting companies. The results of the study partially showed that the variables ROA (Return on Asset) and ROE (Return on Equity) did not have a significant effect on the underpricing value of IPO shares, and simultaneously the variables ROA (Return on Asset) and ROE (Return on Equity) together had a significant effect on the underpricing of IPO shares, where the coefficient results were negative in the underpricing value of IPO shares, which means that the greater the variables ROA (Return on Asset) and ROE (Return on Equity) then The underpricing value of the stock will decrease further.